Potential of gelatin films with silver-kaolin and cinnamon bark oil as primary packaging for packed salad - Idrus Saaidy, Nur Amila Najwa (2021)
The interest in renewable packaging film has increased since the rose of synthetic-based plastics disposal has caused serious issues towards environmental pollution. Active packaging is an alternative solution in improving the shelf life while sustaining the nutrients and quality of food products during storage. Gelatin is a protein that extracted from animals’ skins and bones and has great potential as the renewable sources for packaging films. This research focused on how the physical, mechanical, and water barrier retention of the gelatin film were enhanced as active substances were incorporated into the packaging film for food products. In the first objective, this study discovered the potential application of kaolin (Kln) and silver/kaolin (Ag/Kln) in fish gelatin (FG)- composite films as active packaging material. Three different types of kaolins; raw Kln, Ag/Kln (1:2) mix and Ag/Kln (1:1) mix with various concentrations (15%, 30% and 45%) were prepared by solution casting. For the water barrier properties, the wettability test indicated that the addition of kaolin in gelatin films produced hydrophobic films and lower (p<0.05) water vapour permeability, regardless of the kaolin type and concentration. Scanning electron microscopy images portrayed that higher inclusions of Ag/Kln compounds are able to develop smoother surface and homogenous cross-section. In addition, by incorporating these two materials, films with great antimicrobial effect (p<0.05) towards both Gram-positive and Gram-negative bacteria were produced. Elevation of Ag/Kln concentration also proved to lower (p<0.05) the transmission of ultraviolet-vis light through the films. In the second objective, an active packaging film composed of silver/kaolin-gelatin (FG_Ag/Kln) incorporated with cinnamon bark essential oil (CBEO) of different concentrations (0% as control film, 3%, 6%, and 9%) was established. Increased in CBEO improved the mechanical properties of the films by increasing the Young’s modulus (376.20 to 1637.40 MPa) and tensile strength (3.51 to 32.47 MPa). Additionally, decreases in the water vapour permeability (1.02 to 0.77%), water solubility (8.80 to 7.20%), and moisture content (0.46 to 0.32%) of the films were observed, while the water contact angle for all the films were higher than 100° (116.38 – 123.00°). These findings indicated good wettability, improved hydrophobic properties, and enhanced water retention property of the films as CBEO concentration increased. As CBEO concentration increased, both the Gram-positive and Gram-negative bacteria were also effectively inhibited. These findings indicated the potential of 3-9% CBEO in enhancing the functional properties of FG_Ag/Kln composite film. In the third objective, the application of FG film reinforced with Ag/Kln (1:1) and CBEO as packaging materials was observed and compared. The potential of the packaging film to protect and maintain the quality of ready-to-eat salad (Romaine lettuce) was investigated for 13 days. The overall observations revealed that films contained the highest CBEO incorporation had improved and extended (p<0.05) the shelf life of ready-to-eat salad. Therefore, these findings suggested that FG film with Ag/Kln with CBEO has high potential and beneficial for food packaging applications.